Oleoylethanolamide facilitates PPARα and TFEB signaling and attenuates Aβ pathology in a mouse model of Alzheimer’s disease - Michele M. Comerota; Manasee Gedam; Wen Xiong; Feng Jin; Lisheng Deng; Meng C. Wang; Jin Wang; Hui Zheng (Molecular Neurodegeneration, 2023)
Abstract Background Age is the strongest risk factor for the development of Alzheimer’s disease (AD). Besides the pathological hallmarks of β-amyloid (Aβ) plaques and neurofibrillary tangles, emerging evidence demonstrates a critical role of microglia and neuroinflammation in AD pathogenesis. Oleoylethanolamide (OEA) is an endogenous lipid amide that has been shown to promote lifespan and healthspan in C. elegans through regulation of lysosome-to-nucleus signaling and cellular metabolism. The goal of our study was to determine the role of OEA in the mediation of microglial activity and AD pathology using its stable analog, KDS-5104. Methods We used primary microglial cultures and genetic and pharmacological approaches to examine the signaling mechanisms and functional roles of OEA in mediating Aβ phagocytosis and clearance, lipid metabolism and inflammasome formation. Further, we tested the effect of OEA in vivo in acute LPS-induced neuroinflammation and by chronic treatment of 5xFAD mice. Results We found that OEA activates PPARα signaling and its downstream cell-surface receptor CD36 activity. In addition, OEA promotes TFEB lysosomal function in a PPARα-dependent but mTORC1-independent manner, the combination of which leads to enhanced microglial Aβ uptake and clearance. These are associated with the suppression of LPS-induced lipid droplet accumulation and inflammasome activation. Chronic treatment of 5xFAD mice with KDS-5104 restored dysregulated lipid profiles, reduced reactive gliosis and Aβ pathology and rescued cognitive impairments. Conclusion Together, our study provides support that augmenting OEA-mediated lipid signaling may offer therapeutic benefit against aging and AD through modulating lipid metabolism and microglia phagocytosis and clearance.